A Meier–Gorlin syndrome mutation impairs the loading of the MCM2–7 complex during DNA replication initiation - Yusong Liu; Mengquan Yang; Ping Lu; Haishan Gao; Maozhou He; Yitao Wang; Ao Qi; Ting Cao; Qiuqin Zhang; Shutao Qi; Yigong Shi; Hongtao Yu (Proceedings of the National Academy of Sciences, 2026)
Chromatin loading of the hexameric replicative helicase MCM2–7 complex requires coordinated interactions with the origin recognition complex (ORC), CDC6, and CDT1. MCM2–7 not bound to DNA forms a single hexamer (SH) with an open DNA entry gate between MCM2 and MCM5. Two MCM2–7 SHs can be loaded sequentially to form the double hexamer (DH) that encircles the DNA duplex. Activated MCM2–7 then unwinds DNA and initiates DNA replication. Our cryoelectron microscopy analyses show that a fraction of human MCM2–7 without DNA exists as DH. Unexpectedly, we find that the MCM3 winged helix domain (WHD) docks on MCM2 in both DNA-free DH and SH, creating a safety latch across the DNA entry gate to block DNA entry into the central channel. The safety latch can be opened by ORC-CDC6 binding. Perturbing this latch by structure-based or disease-related mutations of MCM3 causes replication defects and DNA damage checkpoint activation. Shortening the MCM3 linker between the helicase domain and WHD alleviates the cell cycle defects of the latch-strengthening mutation. Our findings uncover a regulated step in MCM2–7 loading with implications for human diseases.